Motiv till fortsatt elitsatsning. - En studie på svenska längdskidåkare utanför a-landslaget. - Byström, A.; Jonsson, A. (Essay in Sport Psychology, 2006)
Cross-country skiing is a physically and psychologically demanding sport, which makes it interesting to study from a motivational perspective. The main purpose of this study was to examine what factors motivate elite cross-country skiers who are not part of the national team to pursue with their elite sport commitment. A secondary aim of the study was to examine what the respondents want to accomplish with their sport commitment and what benefits and costs are related to that commitment. The study included 13 respondents (eight men and five women), with ages ranging from 20 to 30. Semi-structured interviews were conducted with the respondents. Findings indicated that the respondents primarily were motivated by intrinsic motivation, where the social relationships and emotional factors were considered important. Regarding accomplishments, the respondents spoke of an urge to perform during competitions and to develop and improve, demonstrating a combination between task and ego goal orientation. The respondents experienced more benefits than costs connected to elite crosscountry skiing. Recommended for future research is to investigate how economical factors and global warming affect the motivation of elite cross-country skiers.